2012
DOI: 10.5114/wiitm.2012.32384
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized clinical trial of laparoscopic sleeve gastrectomy versus open Roux-en-Y gastric bypass for the management of patients with morbid obesity.

Abstract: IntroductionRoux-en-Y gastric bypass (RYGB) is considered the gold standard bariatric procedure with documented safety and effectiveness. Laparoscopic sleeve gastrectomy (LSG) is a newer procedure being done with increasing frequency. Randomized comparisons of LSG and other bariatric procedures are limited. We present the results of the first prospective randomized trial comparing LSG and RYGB in the Polish population.AimTo assess the efficacy and safety of LSG versus RYGB in the treatment of morbid obesity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 26 publications
4
64
0
Order By: Relevance
“…[24][25][26][27] The present study obtained similar results. The largest BMI reduction at the 6-month follow up was observed for SG (12.29%), and the smallest BMI reduction was observed for LAGB (9.02%).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…[24][25][26][27] The present study obtained similar results. The largest BMI reduction at the 6-month follow up was observed for SG (12.29%), and the smallest BMI reduction was observed for LAGB (9.02%).…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have assessed the use of RYGB and compared its outcomes with those of other bariatric procedures. [24][25][26][27] RYGB was shown to very effectively reduce body weight; however, a higher incidence of complications associated with anastomotic leakage, pulmonary embolism, deep vein thrombosis, as well as frequent wound infections and postoperative hernia was observed. In the present study, the patients were qualified for the procedures on the basis of the current guidelines and a number of tests developed by a specialist panel, as well as consultations and each patient's personal commitment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of obese patients, multiple factors could play a role in male sexual dysfunction, including medical treatment, which can interfere with sexual function, vascular damage due to uncontrolled diabetes or hypertension and lack of self-esteem [4]. Bariatric surgery is an effective treatment option for obese people [7, 8]. At present, laparoscopic sleeve gastrectomy (LSG) and laparoscopic Roux-en-Y gastric bypass (LRYGB) are the most popular types of bariatric operations [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of surgical treatment are not limited only to the reduction of body mass. Results of numerous studies have indicated the reduction of mortality risk in long-term follow-up in the group of patients treated surgically when compared with patients treated conservatively [6,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%